(untitled) (Third Sector Social Economic Review, 2020)
Regional imbalances are observed in almost all developed and developing countries and policies are developed to eliminate the imbalances. Similarly, Turkey has put a variety of policies in effect to reduce the imbalances between the regions.One of the most important policies implemented to reduce the regional imbalances is the establishment of 26 development agencies between the years 2006 and 2009. The purpose of this study is to reveal the potential and weaknesses of the development agencies and to make an evaluation and suggestions accordingly. Within the scope of this study, a questionnaire was applied through e-mail to the specialists working in development agencies. The data obtained from 174 participants were evaluated by a SWOT analysis. The findings of the study are as follows: i) Despite the strengths and opportunities that development agencies have, they have not been able to achieve the expected success due to their weaknesses and threats they have been exposed to. ii) It has been concluded that the agencies can be successful on the condition that the necessary arrangements are made and support is received from local authorities.